Solisti na koncertih Filharmonične družbe do leta 1872 - Železnik, Sara (Muzikološki zbornik, 2013)
Soloist concerts were extremely common at the Philharmonic Society up to the year 1872. The share of local musicians was much larger in relation to foreign soloists. Most common were singers, followed by pianists and violinists. The names of soloists were written very inconsistently. Due to this incomplete information it is not possible to identify precisely all the performers that appeared at the concerts.
Keywords: 19.st.; Filharmonična družba; koncertni sporedi; Ljubljana; solisti